Effects of N-(2-Diethylaminoethyl)-N-(2-hydroxy- 2-phenylethyl)-2,5-dichloroaniline (AN 162) on Platelet Function and Blood Coagulation - Kenzie, R. D Mac; Blohm, T. R (Thrombosis and Haemostasis, 1971)
When AN 162 was added to human citrated platelet-rich plasma at 30-300 µg/ml, it inhibited platelet aggregation induced by adenosine diphosphate, collagen, and thrombin. When AN 162 was given orally to guinea pigs at 30 to 100 mg/kg, an in vivo inhibitory effect on platelet aggregability was found. Though it activated platelet factor 3, the concentration of AN 162 required for substantial activation was greater than that for inhibition of platelet aggregation. No effect on plasma clotting factors was found at or below 300 µg/ml. Slight prolongation of whole blood clotting time was found in the rat and monkey.